Rock support in hydropower projects of Nepal: case studies - Sunuwar, Subas Chandra (Journal of Nepal Geological Society, 2006)
The principal objective of rock support is to assist the rock mass to support itself. One common example is where the rock support system (e.g. rock bolts and shotcrete) actually becomes integrated with the rock mass. Rock support strengthens the rock mass surrounding an excavation by creating a reinforced zone, which maintains the integrity of the excavated surface, possesses sufficient flexibility to allow for the redistribution of stresses around the excavation, and has enough stiffness to minimise the dilation (opening) of discontinuities. Rock mass classification systems are used worldwide as a basis for tunnel support design. The Q and Rock Mass Rating systems have been extensively applied in rock support design on most of the hydropower projects in Nepal. Generic design guidelines based on rock mass classification systems cannot provide suitable rock support for every site. Therefore some modifications are necessary to suite the site-specific ground conditions including local rock mass and geological hazards. There are relatively few tunnels excavated in the tectonically active Nepal Himalaya. Large diameter tunnels in Nepal are commonly lined with concrete whereas recently smaller-diameter tunnels are either shotcrete-lined or left unsupported. "Leaky" lining has been used in most of the projects to avoid the heavy reinforcement needed to withstand the occasional very high external water pressures.